Evaluation of the Use of CBT System in School Examinations in Cluster II Dewi Sartika, East Baturaja District - Sri Fitriyati; Saipul Annur; Houtman (Didaktika: Jurnal Kependidikan, 2024)
This study aims to evaluate the Computer-based Test system in school examinations in Cluster II Dewi Sartika, East Baturaja District. This research was conducted at SD Negeri 11 OKU, which is located at Jl. Jendral A. Yani, Kelurahan Baturaja Lama, District Baturaja Timur, Regency Ogan Komering Ulu. This research is a type of descriptive research with a qualitative approach. Observation, interview, questionnaire, and documentation methods were used to collect data. The data analysis stage includes data reduction, data presentation and conclusion taking. The results showed that the use of Computer Based Test in school examinations at SD Negeri 11 OKU has many benefits both in terms of material and spirituality, including being able to improve school exam results in the education unit itself, being able to make icons or showing the school's identity as a National Level Adiwiyata school for the preparation of facilities and infrastructure classified as quite adequate and adequate human resources. What distinguishes this study from other research is related to research subjects that focus on assessment using CBT and within the scope of elementary schools.